The Sacred and Ethnocultural Code of Kazakh Jewelry Chrematonyms - Kudyarova, Ш.Т.; Kortabayeva, Г.Қ.; Darmenova, А.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
This article explores the names of jewelry items, their mythic-semantic meanings and interpretations, thematic-lexical categories, and usage peculiarities. At the intersection of language and culture, it is crucial to uncover the inner essence, cultural semantics, and sacred-pragmatic significance of archetypal, mythical, and symbolic linguocultural units related to the art of jewelry. Jewelry encodes standards, stereotypes, and symbols that reflect national spirit through metaphors preserved in paremiological and phraseological systems. These culturally marked elements are transmitted from generation to generation, revealing the spiritual worldview of the Kazakh people. The study aims to decode the ethnocultural meanings embedded in women’s adornmentssuch as bracelets (bilezik), facial beads (betmonshak), rings (zhuzik, sakinа), pendants (zhyrga), earrings (syrga), buttons (tuyme), hair ornaments (shashbau), and decorative chains (sholpy, shytyra)through data preserved in phraseology and paremiology. These jewelry items are not only indicators of beauty or wealth but also serve as ritualistic, mythical-sacred, and functional objects, with their traditional use, age-specific variations, and practical applications considered key subjects of study. Additionally, jewelry is examined as a historical source, with attention to its functional meanings, regional features, and distinctions based on age.